Bridging perspectives: The value of collaboration between Traditional Healing Practitioners and Medical Doctors in dementia research and care in South Africa - Mc Glinchey, Eimear (My University, 2025)
Introduction: Traditional Healing Practitioners (THPs) provide care to the majority of the population in South Africa. Despite their widespread presence, they remain largely excluded from dementia research and policy. This reinforces healthcare inequities and overlooks the realities of communities where THPs provide care. Methods: This paper explores the role of THPs in dementia care by examining literature in South Africa. It identifies key barriers to collaboration between THPs and medical doctors and discusses pathways for integration. Results: Barriers include epistemological historical marginalization, mutual distrust, fragmented care pathways, and language barriers. These challenges hinder knowledge exchange and joint dementia care strategies. Discussion: Strengthening relationships through structured engagement, bidirectional knowledge exchange, and ethical collaboration could bridge the gap between THPs and Medical Doctors (MDs). A pluralistic, integrated model valuing both systems could lead to more equitable and effective dementia care. Highlights: The majority of people in South Africa engage with Traditional Healing Practitioners (THPs) as part of their healthcare, yet THPs remain largely excluded from dementia research and policy. Barriers to collaboration between THPs and Medical Doctors (MDs) include historical marginalization, mutual distrust, fragmented care pathways, and language differences. Integrating THPs and MDs through structured engagement, bidirectional knowledge exchange, and ethical collaboration could enhance dementia care. Shifting away from the binary opposition of Indigenous Knowledge Systems (IKS) and biomedical approaches toward a more integrated and collaborative model of dementia care could lead to more equitable and effective healthcare. The FUNDISA (Framework for Understanding Neurocognitive Disorders via Indigenous Systems in South Africa) project aims to understand how dementia is conceptualized by THPs and foster collaboration between THPs and MDs to support effective dementia care.
PUBLISHED
Keywords: Indigenous Knowledge Systems; South Africa; Traditional Healing Practitioners; dementia care; pluralistic healthcare